Two fungal flavonoid-specific glucosidases/rutinosidases for rutin hydrolysis and rutinoside synthesis under homogeneous and heterogeneous reaction conditions - Kotik, Michael; Javůrková, Hana; Brodsky, Katerina; Pelantová, Helena (AMB Express, 2021)
The glycosidases within GH5-23 cleave the glycosidic bond of β-glucosylated or rutinosylated flavonoids. Moreover, by virtue of their transglycosylation activity, glycoconjugates with glucosyl and rutinosyl moieties are accessible. Here we report the biochemical characterization and biotechnological assessment of two heterologously expressed members of GH5-23-McGlc from Mucor circinelloides and PcGlc from Penicillium chrysogenum. Both enzymes exhibited the highest hydrolytic activities with quercetin-3-β-O-glucopyranoside, whereas lower specificity constants were determined with the rutinosides narcissin, rutin and hesperidin. High stabilities against thermal, ethanol and dimethyl sulfoxide-induced inactivation, a very limited secondary hydrolysis of the formed transglycosylation products, and no detectable product inhibition were additional features appropriate for biotechnological applications. The enzymes were compared in their efficiencies to hydrolyze rutin and to synthesize 2-phenylethyl rutinoside under homogeneous and heterogeneous reaction conditions using high rutin concentrations of 100 and 300 mM. Highest transglycosylation efficiencies were achieved with fully dissolved rutin in reaction mixtures containing 25% dimethyl sulfoxide. Molecular docking and multiple sequence alignments suggest that the hydrophobic environment of aromatic residues within the + 1 subsite of GH5-23 glycosidases is very important for the binding of flavonoid glucosides and rutinosides.
Keywords: Dimethyl sulfoxide; Transglycosylation; Flavonoid glycoside; Enzyme stability; Process optimization; Solubility